Multimorbidity: a global public health challenge : Multimorbidity - Rajović, Nina; Milic, Natasa (Medicinski podmladak, 2024)
According to available data, at least 50 million people in the European Union live with multimorbidity. The trend of an aging population, accompanied by the adoption of unhealthy lifestyles and the rising incidence of chronic illnesses, results in a increase in the occurrence of multimorbidity.This trend has proved to be a major challenge for healthcare systems worldwide. To effectively address the strain on healthcare systems caused by multimorbidity, it is imperative to prioritize the establishment of well-structured, adequately equipped, and appropriately trained primary care teams. Healthcare should be proactive and include a preventive component for patients at risk of multimorbidity. Furthermore, primary healthcare should establish a network with other levels in the healthcare system, including the system of education and social protection programs. This integration should extend to the entire local community, aiming to enhance the well-being of both the individual and the community as a whole. Multimorbidity has show to be a significant obstacle for healthcare systems worldwide, making a need for guidance among health policy makers, health managers and physicians in defining and implementing interventions aimed at decreasing the burden associated with multimorbidity.
Keywords: multimorbidity; health care system; primary health care